(untitled) (Movimenta (ISSN 1984-4298), 2022)
Health care processes have undergone changes due to the current pandemic scenario, creating social isolation measures to contain the virus. The need for continuity in health care is understood, with remote care being regulated in Brazil on an emergency basis due to the COVID-19 pandemic. However, it is a new modality for physiotherapists and patients, resulting in barriers to its implementation. The aim of this research is to analyze the main barriers encountered in the practice of physical therapists in the adoption of telephysiotherapy during the COVID-19 pandemic in Brazil. It is classified as a cross-sectional study, virtual research, quantitative approach, involving 135 physical therapists in clinical practice, residing in Brazilian territory, 84%, feel adapted to the remote modality of care, despite reporting difficulties such as: lack of affinity with technological resources, followed by patients’ understanding of the guidelines given by the physiotherapists. Through the identification of the main barriers faced in the implementation of telephysiotherapy, it is possible to point out that they enable the improvement of remote care in Brazil. Thus, there is a need for more studies that enhance the discussion and favor decision-making in this area to expand knowledge.